The results of modeling the strain state of soil base reinforced by soil-cement elements under strip foundations of the building - Vynnykov, Yuriy; Razdui, Roman (Academic journal Industrial Machine Building Civil Engineering, 2022)
The results of complex experimental and theoretical researches of the deformed state of the system "soil-in-situ – soil-cement base – strip foundation – brick building" with layers of weak clay soils are given. By comparing the data of finite element method (FEM) modeling in a three-dimension task using an elastic-plastic soil model of the deformed state of the natural (with layers of weak clay deposits) and reinforced with vertical soil-cement elements (SCE) base of strip foundations of the five-section 9-10-story building, as well as the results of long-term (over 10 years) geodetic observations of this real object proved the correctness of using embedded beam pile elements to simulate SCE. The effectiveness of the SCE reinforcement method for improving soil bases with a low deformation modulus has been confirmed.